1972
DOI: 10.1515/bchm2.1972.353.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Alterationen im Testosteronstoffwechsel als Folge einer fehlgeleiteten sexuellen Entwicklung der Ausstattung der Rattenleber mit Enzymen des Steroidhormonstoffwechsels

Abstract: Zusammenfassung:In Inkubationsversuchen mit 2. Im Metabolit-Muster gibt sich die Feminisierung Leberschnitten wurde der Stoffwechsel von Testo-der behandelten Tiere in einer gegenüber den steron studiert, und zwar bei sexuell normal ent-Kontrolltieren signifikant kleineren Bildungsrate wickelten, 130 Tage alten männlichen Ratten und (Faktor 0,15) von Androstendion und einer signibei gleichaltrigen und gleichgeschlechtlichen Ratten fikant größeren Produktionsrate von 5a-konfigunach Eingriff in die sexuelle Entw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1973
1973
1973
1973

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The authors explain the phenomenon by postulating that estrogen blocks either the neonatal secretion or the action of testosterone. In the same type of male animals the steroid A4-3-keto reduction was also feminized (71). Eimrsson et al recently have reported a feminine pattern in hydroxylation and A4-3-keto reduction of androstenedione and progesterone in liver micro somes of male pseudohermaphrodite rats (22).…”
Section: Sex Differences In Steroid Metabolism In the Rat Liver Are Pmentioning
confidence: 86%
See 1 more Smart Citation
“…The authors explain the phenomenon by postulating that estrogen blocks either the neonatal secretion or the action of testosterone. In the same type of male animals the steroid A4-3-keto reduction was also feminized (71). Eimrsson et al recently have reported a feminine pattern in hydroxylation and A4-3-keto reduction of androstenedione and progesterone in liver micro somes of male pseudohermaphrodite rats (22).…”
Section: Sex Differences In Steroid Metabolism In the Rat Liver Are Pmentioning
confidence: 86%
“…Taken from Denef and De Moor, 1968 (16). manently decreased to female levels in males treated with a high dose of estrogen at birth (28,70,71). The authors explain the phenomenon by postulating that estrogen blocks either the neonatal secretion or the action of testosterone.…”
Section: Sex Differences In Steroid Metabolism In the Rat Liver Are Pmentioning
confidence: 99%